Effect of maternal education on the literacy-numeracy development of children: A propensity-score matched analysis - Md Akter Hosen; M. Iftakhar Alam; Mohaimen Mansur (PLoS ONE, 2026)
This study examined the causal relationship between maternal education and children’s literacy-numeracy development in Bangladesh using nationally representative data from the Bangladesh Multiple Indicator Cluster Survey. The analysis focused on 9,454 children aged 3–4 years. To strengthen causal inference, we applied propensity score matching, which reduces selection bias by balancing observed covariates between groups. From the analysis, we found that the average treatment effect of the treated was almost 18.4%, which means after matching, the probability of literacy-numeracy development in children was 18.4% higher among the mothers who had higher level of education compared to the same mothers had they not higher level of education. Subgroup analyses further revealed heterogeneity by place of residence: the effect of maternal education was stronger in urban areas (26.2%) than in rural areas (16.3%), suggesting that contextual factors may amplify or constrain the benefits of maternal education. These findings provide an evidence of the critical role of maternal education in early childhood development.